WHERE WE STAND: ANALYSIS OF AMBULANCE SERVICES OF KARACHI. - RAZA, SHAHID; AHMED, Dr.KAZI AFAQ (The journal of contemporary issues in business and government, 2021)
Around 20 ambulance services operated in Karachi; however, the network of Edhi, Chhipa and Aman ambulance services provides the bulk of patient transport. The study aims to compare the quality of ambulance service delivery with international standards. With a mix- method approach, 357 patients/attendants and key stakeholders participated in the study. The results revealed a wide range of differences in service quality. Aman services delivery quality is rated 72% compliant, but it constitutes less than 20% of the share of inpatient transportation due to limited ambulances while Edhi and Chhipa contribute 80% of patient transportation, but their service delivery quality is rated only 13%. In the subset of monitoring, infection control, and medicine, Edhi & Chhipa services meet 0% standards. The thematic analysis revealed that the primary reasons for the poor quality are lack of legislation & minimum standards, Poor or no monitoring, financial constraints, and lack of awareness. In conclusion, the ambulances services operating in the city lacks minimum service quality standards, thus pose a constant threat to patient life using these services.